CPT112 – Discrete Structures (Struktur Diskrit) - February/March 2022 - PPSKOM, Pusat Pengajian Sains Komputer (2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 CPT112 – Discrete Structures (Struktur Diskrit)